The relationship between physical exercise and suicidal ideation in college students: chain mediating effect of basic psychological needs satisfaction and sense of meaning in life - Ou, Yayi; Guo, Kelei; Cheng, Yueming (Frontiers in Psychology, 2025)
ObjectiveTo explore the relationship between physical exercise and suicidal ideation of college students, and the mediating role of basic psychological needs satisfaction and sense of meaning in life.MethodsA stratified cluster random sampling method was adopted to survey 1,008 college students of Zhaoqing University from January 17th to 27th, 2024. The Physical Exercise Scale, Suicidal Ideation Scale, Basic Psychological Needs Satisfaction Scale, and Life Meaning Scale were used to assess physical exercise, suicidal ideation, basic psychological needs satisfaction, and sense of meaning in life, respectively. Data were statistically analyzed using descriptive statistics, correlation analysis, regression analysis, and mediation analysis using SPSS (IBM Corp.).ResultsPhysical exercise was negatively associated with suicidal ideation (r = −0.26, p < 0.01). A significant direct effect was observed between physical exercise and suicidal ideation (β = −0.17, p < 0.01, 95% CI [−0.24, −0.11]). Physical exercise positively predicted both basic psychological needs satisfaction (β = 0.27, p < 0.01, 95% CI [0.20, 0.32]) and sense of life meaning (β = 0.17, p < 0.01, 95% CI [0.11, 0.22]). Both basic psychological needs satisfaction (β = −0.17, p < 0.01, 95% CI [−0.24, −0.10]) and sense of meaning in life (β = −0.12, p < 0.01, 95% CI [−0.20, −0.05]) were negatively associated with suicidal ideation. Additionally, basic psychological needs satisfaction was positively associated with sense of meaning in life (β = 0.53, p < 0.01, 95% CI [0.48, 0.58]). Mediation analysis revealed that both basic psychological needs satisfaction and sense of meaning in life significantly mediated the relationship between physical exercise and suicidal ideation. The mediating effect consists of three paths: the independent mediation effect of basic psychological needs satisfaction (effect value is −0.04), the independent mediation effect of sense of meaning in life (effect value is −0.02), and the chain mediation effect of basic psychological needs satisfaction and sense of meaning in life (effect value is −0.02).ConclusionThis study found that physical exercise is negatively associated with suicidal ideation among college students. Furthermore, this relationship is explained through two key mechanisms: the mediating role of basic psychological needs satisfaction, and the sequential mediation pathway involving both basic psychological needs satisfaction and sense of meaning in life. These findings highlight the importance of promoting physical exercise to enhance mental health and mitigate suicidal ideation risk in college populations.